Indonesian English Teachers’ Narratives on Adapting to Curriculum Change - Naufal Mufatih Al Fikri; Willy Prasetya (IJECA (International Journal of Education and Curriculum Application), 2024)
Curriculum change has occurred multiple times in Indonesia. The latest curriculum change to Kurikulum Merdeka (Emancipated Curriculum) posed some challenges and difficulties among teachers because they were required to implement the curriculum and any policies from the central government in a relatively short time. The present study aims to describe how two Indonesian EFL teachers adapted to such curriculum change. Two English teachers with over a decade of experience were involved. One taught at a vocational high school in a rural area, focusing on practical English. The other taught at an urban school, emphasizing academic English. To collect the narratives, semi-structured interviews were conducted. Thematic analysis with predefined themes based on Fullan's theoretical framework was applied to point out unique data patterns that would shed some light on how the two participants adjusted themselves and their practices in response to changes in curricular policies. This study will examine how teachers adapted to rapid curricular changes in Indonesia, including the challenges they faced, the support they received, and the strategies they employed, such as the utilization of online resources like YouTube.